Cloning and sequencing of the genes encoding coat protein (CP) in Potato virus Y from Thai Nguyen province - Tam, Nguyen Thi; Mau, Chu Hoang; Thanh Thanh, Nguyen Vu (Academia Journal of Biology, 2012)
Potato (Solanum tuberosum L.) is the most widely distributed crop in tropical and subtropical zones of the world. Among diseases potato viruses play major role in reducing the yield. PVX (Potato virus X), PVY (Potato virus Y), PLRV (Potato leaf roll virus), PVA (Potato virus A), PVM (Potato virus M), PVS (Potato virus S) are major viral diseases occurring in Vietnam. PVY (Potato virus Y) is the type member of the genus Potyvirus of the family Potyviridae. The virus has a long filamentous particle containing one single-stranded, positive sense RNA genome of approximately 9.7 kb. PVY is an important pathogen infecting potato, tobacco, tomato and other solanaceous plant species. Different potato PVY isolates occur that can be categorized in 5 groups: PVYO, PVYN, PVYNTN, PVYNWi and PVYC. In this paper we report cloning and sequencing of coat protein (CP) gene of PVY from Thai Nguyen potato. The CP gene of this isolate was found to be 801 nucleotides long, coding for 267 amino acids. Comparison amino acid of CP protein in potato from Thai Nguyen with ten sequences on NCBI showed that amino acid was 92.1-98.9% homology.